Squamous Cell Carcinomas of the Skin Explore Angiogenesis-Independent Mechanisms of Tumour Vascularization - Ievgenia Pastushenko; Tamara Gracia-Cazaña; Sandra Vicente-Arregui; Gert G. Van den Eynden; Mariano Ara; Peter B. Vermeulen; Franciso José Carapeto; Steven J. Van Laere (Journal of Skin Cancer)
Aims. To evaluate the vascularization in basal cell carcinomas (BCCs) and squamous cell carcinomas (SCCs) of the skin. Methods. We performed CD31 (i.e., panendothelial marker) and CD105 (i.e., proliferating endothelium marker) immunostaining on samples of 70 SCCs and 70 BCCs of the skin. We evaluated the relative blood vessel area using the Chalkley counting method in each histologic subtype of these tumours. We calculated the degree of proliferation of blood vessel endothelium dividing CD105-Chalkley score by CD31-Chalkley score. Results. We found significantly higher peritumoral and intratumoral blood vessel area in SCC when compared to BCC (both with CD31 and CD105). Chalkley counts differed significantly between groups with different BCC histologic subtypes and SCC with different grade of differentiation. Surprisingly, the degree of proliferation of blood vessel endothelium was higher in BCC when compared to SCC. Conclusions. While SCC exhibited significantly higher intratumoral and peritumoral blood vessel areas compared to BCC, the relatively low rate of proliferating endothelium in this tumour type suggests the existence of endothelial-sprouting-independent mechanisms of vascularization in SCC.